The factors that influence consumers to purchase smartphones: UiTM (Melaka) Kampus Bandaraya / Nor Fardiana Ahmad and Nur Hazwani Mohd Jama - Ahmad, Nor Fardiana; Mohd Jama, Nur Hazwani (Faculty of Business and Management, 2016)
Smartphone is an important item that can connect people around the world. With this development and evolution in nation country, it becomes phenomenon and impact in generation to generations. People become more stylish and trendier by using sophisticated items in daily life. People also have high desired in their lifestyle so it creates more beliefs, preferences and behaviors in their needs and wants. In this study, 162 questionnaires were distributed to BBA Marketing students in UiTM (Melaka) Kampus Bandaraya. The findings of this study were obtained where the Pearson Correlation Analysis result confirmed relationships between purchase intentions with independent variables, such as price, compatibility, relative advantage, and social influences. The purpose of this research is to identify the factors that influence consumers to purchase smartphone among the young generation from BBA Marketing students in UiTM (Melaka) Kampus Bandaraya. Using questionnaire, all respondent cooperated to answer question regarding their agreeableness and disagreeableness toward statement. Result were obtained and presented in the reliability analysis, frequency analysis, descriptive statistics, correlation analysis (Pearson Correlation Analysis) and multiple regression analysis. The result shows that all the four factors have significant relationship towards consumer purchase intention.